Proceedings of International Conference on Computational Intelligence and Data Engineering Proceedings of ICCIDE 2018 - Chaki, Nabendu; Devarakonda, Nagaraju; Sarkar, Anirban; Debnath, Narayan C. (Lecture Notes on Data Engineering and Communications Technologies,, 2019)
The book presents high-quality research work on cutting-edge technologies and the most-happening areas of computational intelligence and data engineering. It includes selected papers from the International Conference on Computational Intelligence and Data Engineering (ICCIDE 2018). The conference was conceived as a forum for researchers from academia and industry to present and share ideas and results and allow them to develop a comprehensive understanding of the challenges of technological advancements from different viewpoints. As such, this book helps foster strong links between academia and industry. It covers various topics, including collective intelligence, intelligent transportation systems, fuzzy systems, Bayesian network, ant colony optimization, data privacy and security, data mining, data warehousing, big data analytics, cloud computing, natural language processing, swarm intelligence, and speech processing. .